MEF2 and the Right Ventricle: From Development to Disease - Clapham, Katharine R.; Singh, Inderjit; Capuano, Isabella S.; Rajagopal, Sudarshan; Chun, Hyung J. (Frontiers in Cardiovascular Medicine, 2019)
Pulmonary arterial hypertension is a progressive and ultimately life-limiting disease in which survival is closely linked to right ventricular function. The right ventricle remains relatively understudied, as it is known to have key developmental and structural differences from the left ventricle. Here, we will highlight what is known about the right ventricle in normal physiology and in the disease state of pulmonary arterial hypertension. Specifically, we will explore the role of the family of MEF2 (myocyte enhancer factor 2) transcription factors in right ventricular development, its response to increased afterload, and in the endothelial dysfunction that characterizes pulmonary arterial hypertension. Finally, we will turn to review potentially novel therapeutic strategies targeting these pathways.